Influence of Outdoor and Adventure Activities on Subjective Measures of Resilience in University Students. (September 2019) - Kelly, John
Background: Adventure experiences offer opportunities to improve resilience by exposure to controlled challenging situations. While previous studies have shown improvements in resilience, they have often lacked matched control groups, relied on a single measure of resilience, and had limited longitudinal follow-up.Purpose: This research assessed changes in subjective measures of resilience in response to adventure experiences.Method/Approach: Using a quasi-experimental design, resilience was assessed in two matched groups of university students using two validated instruments. Measurements were taken at four time points over a 3-month period, which included a 4-day residential experience for the Outdoor Adventure group.Findings/Conclusion: Adventure experiences showed tentative evidence for influencing subjective measures of resilience, more so for individuals who started with a low score. Resilience demonstrated the largest increase immediately post-program, returning to near baseline within 3 weeks.Implications: The mechanism for change in resilience would appear to be appropriate levels of challenge, rather than specific exposure to outdoor adventure activities. Furthermore, individuals with initially low scores are likely to achieve the greatest gain.